Dobry, zły i brzydki. Fuck For Forest Michała Marczaka w obiegu społecznym i medialnym - Piepiórka, Michał (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2018)
Michał Marczak’s documentary Fuck For Forest was met with interest by both audiences and the media. This was due to the movie’s theme: the documentary tells the story of a group of activists living in Berlin who raise funds for environmental protection through a porn website. The film‘s premiere in Poland was accompanied by an aura of scandal, and Marczak’s movie was criticized by many for supposedly promoting pornography. The article analyzes the strategy used to promote the film in Poland and discusses various forms of commentary and media discourse on the film.